Studying and Generation of Saffron Flower's 3D Solid Model. (2015) - Zeraatkar, Mojtaba; Khalili, Khalil; Foorginejad, Abolfazl
Abstract: Because of having non-rigid parts in various and complicated shapes and high level of variability in their shapes, plants have remained one of the most difficult objects to be modeled. Saffron is the most expensive agriculture crop and spice in the world. There is very few information about physical and geometric properties of Saffron flower. In this article, using reverse engineering, 3D data of Saffron flower are extracted by using laser scanner, and after data processing, using some techniques and algorithms, the 3D model of Saffron flower was developed.